Desenvolvimento de método empregando microextração líquido-líquido dispersiva em fase reversa para determinação de Ca, Mg, Na e K em diesel - Witcel, Cristiane (2017)
A reversephase dispersive liquidliquid microextraction (RPDLLME) method was developed for the extraction and preconcentration of Na, K, Ca and Mg in diesel oil for further determination by flame atomic absorption spectrometry (FAAS). For the extraction of the analytes a mixture of two solvents, dispersant / extractor was used. The extraction of the analytes occurred after addition of the dispersant / extractor mixture and the sedimented phase was formed by centrifugation. Preliminary analyzes showed that there is no need to use ultrasound in the extraction of analytes. The spin time was set to 10 minutes. Then, complete experimental planning 252 was performed. In the fractional factorial design, we studied: temperature for extraction of the analytes (X1: 60, 70 and 80 °C); mass of samples (X2: 5, 10 and 15 g); volume of the dispersant / extractor mixture (X3: 0.5, 1.0 and 1.5 mL); (X4: 1.0, 1.5 and 2.0 molꞏL1) and dispersant / extractor ratio (X5: 60, 70 and 80%, v/v). By the analysis of effects it was verified that X1 and X2 had significant effects, they were studied in the DCCR at levels X1: 60; 63; 70; 77 and 80 °C, and X2: 5; 6; 8.5; 11 and 12 g. The variables X3, X4 and X5 were fixed in 1.0 mL; 1 mgꞏL1 and 80%, respectively. With the analysis of the DCCR, a model was obtained, which was experimentally validated. From the response surface, the optimal values for Temperature 72.06 ºC and Sample Mass 10.34 g were obtained. The analytical calibration curves were linear between 0.1 and 2.0 mg L1 The quantification limits for Na, K, Ca and Mg for this method were 0.13; 0.27; 0.17 and 0.02 mgꞏkg1, respectively. Accuracy was assessed by means of recovery trials ranging from 96,55 to 103,45% with RSD less than or equal to 5%. The method developed was considered feasible for the determination of Na, K, Ca and Mg.